Implementasi Asesmen Proses di Pendidikan Anak Usia Dini Al-Islam Riyadhul Irfan Kecamatan Kadungora - Siti Aliyah; Ade Rosita; Nova Nurul Huda (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2026)
Law Number 20 of 2003 concerning the National Education System, Article 1 paragraph 14 states that Early Childhood Education (PAUD) is "an effort to foster children from birth to the age of six years which is carried out through the provision of educational stimulation to help physical and spiritual growth and development so that children are ready to enter further education. Early childhood education is carried out through formal, non-formal and informal channels. In the independent curriculum there are 2 learning processes. There are two assessment categories: Formative Assessment and Summative Assessment. Formative assessment is designed to provide feedback and information to educators and students, which facilitates improvements in the learning process. The purpose of this study is to describe the Implementation of Process Assessment and the obstacles and challenges in the implementation of process assessment at PAUD Al-Islam Riyadhul Irfan, Kadungora District. This study uses a qualitative descriptive method. Based on the results of research related to the Implementation of process assessment at PAUD Al Islam Riyadhul Irfan, Kadungora District, it focuses on the assessment of child development carried out when the learning process is taking place, not just on the final results. Implementation of process assessment at PAUD Al Islam Riyadhul Irfan includes 7 steps of activities, including: formulating/determining activities, preparing assessment tools, determining assessment criteria, collecting data, determining values, reporting assessment results and following up on assessment results.   Keywords: Early Childhood, Formative Assessment, Process Assessment